The Effectiveness of Spiritual Parenting Training in Enhancing Parental Self-Efficacy among Working Mothers - Ihda Al Husnayaini; Syamsul Bachri Thalib; M. Ahkam Alwi; Ahmad Razak; Abdul Saman (ILIN Institute Makassar, 2026)
Working mothers face various role demands in their lives, making them more susceptible to role conflicts that can affect their self-confidence in providing parenting and education to their children, also known as parental self-efficacy. One of the factors that influences the level of parental self-efficacy is their knowledge and values of beliefs. Spiritual parenting training is one of the efforts aimed at increasing parental self-efficacy. This study aims to examine the effectiveness of spiritual parenting training as an effort to increase parental self-efficacy in working mothers in Makassar City. This study used a quasi-experimental design with a one-group pre-test post-test model involving 10 participants. The measuring instrument used was the parental self-efficacy scale with a reliability value of 0.990. The results of the study reveal an increase in parental self-efficacy with an average pre-test score of 102 and a post-test score of 128. Data analysis was conducted using the Wilcoxon signed rank test technique with a significance value of 0.0025 (p < 0.05). The spiritual parenting training increases awareness of the importance of mothers’ roles and the commitment to parenting, which has an impact on the increase of parental self-efficacy of working mothers in Makassar City.